PENGARUH LABORATORIUM VIRTUAL BERBASIS APLIKASI ANDROID TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATERI METABOLIME FASE F SMAN 1 SUNGAI LIMAU - Petriana, Fania; Yogica, Relsas; Ardi; Olvia Rahmi, Fitri (Jurnal Biogenerasi, 2024)
This research aims to test the effect of an Android application-based virtual laboratory on students' cognitive learning outcomes in F phase metabolism material at SMAN 1 Sungai Limau. This research was conducted in November 2024. The research method used was a quasi-experiment (Quasi Experiment Research) with a Posttest Only Control Group Design research design. The population of this research is all phase F students of SMAN 1 Sungai Limau in the 2024/2025 academic year. Samples were taken using purposive sampling technique. This research data is in the form of student learning outcomes in the cognitive domain. The research instrument used was a test instrument in the form of multiple choice questions. Data from the results of the test instrument were analyzed using the t test with the help of Microsoft Excel 2010. The results of research in the cognitive domain showed that the average score for the experimental class was higher than the control class. The hypothesis was tested via the t test, obtained a value of tcount = 5.005 and ttable = 1.703. Thus, it can be concluded that the Android application-based virtual laboratory has a significant positive influence on students' cognitive learning outcomes in phase F metabolism material at SMAN 1 Sungai Limau.